Single nucleotide polymorphism for certain genes involved in gestational diabetes with risk factors and complications positive - Nor Azlin Mohamed Ismail,; Norkhatijah Mohd Aris,; Zaleha Abdullah Mahdy,; Shuhaila Ahmad,; Norzilawati Mohd Naim,; Harlina Harlizah Siraj,; Rohana Jaafar,; Shareena Ishak,; Roslan Harun,; Abd Rahman Abd Jamal,; Wan Zurinah Wan Ngah,; Syed Zulkifli Syed Zakaria, (Universiti Kebangsaan Malaysia, 2013)
Gestational Diabetes Mellitus (GDM) is associated with pregnancy complications, however its mechanism has not been fully understood. The aim of this study was to investigate the single nucleotide polymorphism (SNP) for identifying candidate genes involve in risk factors and complications of GDM. A total of 174 pregnant women with GDM and 114 healthy pregnant women were genotyped with 384 SNPs from 236 genes. The SNPs identified were rs10946398 (CDKAL1) in GDM risk factors; rs328 (LPL) and rs1042778 (OXTR) in complications of caesarean section; rs5404 (SLC2A2), rs5400 (SLC2A2) and rs13306465 (IRS1) for neonatal intensive care admission. Whereby SNPs rs12255372, rs7901695 and rs7903146 from TCF7L2 gene had six times higher risk (OR, 6.40-6.53) for T2DM at postpartum. In conclusion, although the above SNPs were identified with GDM risk factors and complications among pregnant Malaysian women with GDM, a larger study is needed to ascertain this candidate genes actual association.